En búsqueda de un sindicalismo “moderno”: reformismo sindical y formación política en los años sesenta en Argentina - Gabriela Scodeller (Centre de Recherches sur les Mondes Américains, 2015)
Interested in analyzing in a transnational perspective those systematized experiences of trade union training developed in Argentina during the long sixties; departing from an experience developed within the CGT, this article seeks to scrutinize the interests from which a fraction of the Argentine unionism arose these training processes during this convulsed period and, at the same time, to elucidate its initiative in building international relations in the matter – not exempt from certain dynamics of resignification and reappropriation with a local view of the educational guidelines promoted by labor international organizations.